2016
DOI: 10.3892/ol.2016.5127
|View full text |Cite
|
Sign up to set email alerts
|

HOTAIR, a long non-coding RNA driver of malignancy whose expression is activated by FOXC1, negatively regulates miRNA-1 in hepatocellular carcinoma

Abstract: Abstract.Evidence is rapidly accumulating that long non-coding RNAs (lncRNAs) are involved in human tumorigenesis and are dysregulated in multiple cancers, including hepatocellular carcinoma (HCC). lncRNAs can regulate essential pathways that contribute to tumor initiation and progression with tissue specificity, which suggests that lncRNAs may be valuable biomarkers and therapeutic targets. HOX transcript antisense intergenic RNA (HOTAIR) has previously been demonstrated to be an oncogene and a negative progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 43 publications
1
44
0
Order By: Relevance
“…The mechanism of this feedback loop was explored in the present study, and it was observed that miR-1 regulates the expression of HOTAIR by directly binding to target sites within the HOTAIR sequence. This is consistent with results in hepatocellular carcinoma [38]. All these data suggest that HOTAIR can bind miR-1 and subsequently contributes to the regulation of AMI.…”
Section: Discussionsupporting
confidence: 80%
“…The mechanism of this feedback loop was explored in the present study, and it was observed that miR-1 regulates the expression of HOTAIR by directly binding to target sites within the HOTAIR sequence. This is consistent with results in hepatocellular carcinoma [38]. All these data suggest that HOTAIR can bind miR-1 and subsequently contributes to the regulation of AMI.…”
Section: Discussionsupporting
confidence: 80%
“…A significant number of lncRNAs have been identified to be able to participate in metastasis and proliferation regulation by interacting with miRNA, such as HOTAIR (HOX antisense intergenic RNA) [35, 36] and XIST (X-inactive specific transcript) [37, 38]. In this study, we found that CRNDE was highly expressed in colorectal cancer tissue and colorectal cancer cells, while miR-217 expression was low in colorectal cancer tissue and colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 50%
“…High expression of HOTAIR in HCC tissues and cells was observed in multiple studies . In vivo experiments revealed that the overexpression of HOTAIR can effectively promote HepG2 cell growth . The knockdown of HOTAIR inhibited cell proliferation and induced G0/G1 cell cycle arrest in Huh7 hepatocellular carcinoma cells .…”
Section: Discussionmentioning
confidence: 96%